Prioritization Scheme for Proposed Road Weather Information System Sites: Montana Case Study - Al-Kaisy, Ahmed; Ewan, Levi (Frontiers in Built Environment, 2017)
A model for prioritization of new proposed environmental sensor station (ESS) sites is developed and presented in this paper. The model assesses the overall merit (OM) of a proposed ESS site as part of a Road Weather Information System (RWIS) using weather, traffic, and safety data among other variables. The purpose of the proposed model is to help in selecting optimum sites for new ESS locations, which is important in guiding RWIS system expansion. Inputs to the OM model include weather index (WI), traffic index (TI), crash index, geographic coverage, and opportunistic factors. The WI at a proposed site is determined using multiple indicators of weather severity and variability. The crash index, another major input to the OM model, incorporates crash rate along the route and the percentage of weather-related crashes over the analysis period. The TI, in turn, reflects the amount of travel on the highway network in the area surrounding the proposed ESS site. The fourth input to the merit model accounts for the ESS existing coverage in the area where the proposed site is located, while the fifth and last input is concerned with the availability and ease of access to power and communications. Model coefficients are represented by weights that reflect the contribution of each input (variable) to the OM of the ESS site. Those weights are user-specified and should be selected to reflect the agency preferences and priorities. The application of the proposed merit model on sample sites in Montana demonstrated the utility of the model in ranking candidate sites using data readily available to highway agencies.